2002
DOI: 10.1046/j.1440-6047.11.s6.1.x
|View full text |Cite
|
Sign up to set email alerts
|

Global nutrition problems and novel foods

Abstract: The world's demand for food is becoming greater than ever. The current world population of 6 billion will exceed 8 billion in 2025 and new innovations are needed to meet the growing challenges of the poor and hungry world. Novel foods produced through biotechnology may help alleviate the problems of poverty and food insecurity, but only if steered by continual policy development and actions at the regional, national and international levels. The great progress made with iodized salt in combatting iodine defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
(51 reference statements)
0
22
0
2
Order By: Relevance
“…Increasing food insecurity in the developing world paradoxically has resulted in increasing numbers of overweight. Past studies cite increased availability of high sugar and energy, low fibre foods as a major cause for overweight and obesity [16,17]. However, some studies conducted in developed countries have consistently shown that mild but not severe food insecurity is associated with obesity among women [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing food insecurity in the developing world paradoxically has resulted in increasing numbers of overweight. Past studies cite increased availability of high sugar and energy, low fibre foods as a major cause for overweight and obesity [16,17]. However, some studies conducted in developed countries have consistently shown that mild but not severe food insecurity is associated with obesity among women [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Most of this increase (93%) will take place in the developing world. So new innovations (novel foods, nutrigenomics, biosolutions) are needed to meet the growing challenges of malnutrition in the poor and hungry world (Clugston 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition transitions are also causing increased rates of chronic diseases (e.g., cancer, heart disease, diabetes, obesity, osteoporosis, etc.) in many rapidly developing nations where societies are switching from traditional diets to more calorie-rich diets derived from adopting developed nation's food systems [11,12].…”
Section: Agriculture and Nutrition: The Nexus For Good Healthmentioning
confidence: 99%